Estilo de aprendizaje analítico y logro de la competencia lee diversos tipos de textos en su lengua materna en estudiantes de secundaria de la Institución educativa N° 60520 Miguel Grau seminario, Nauta 2022 - Pacaya Taricuarima, Elisvan (2023)
The most relevant aspects of the research that had as general objective was to relate the analytical learning style and the achievement of the competence read various types of texts in their mother tongue in high school students of the Educational Institution No. 60520 are briefly presented. Miguel Grau Nauta Seminar in 2022, having as hypothesis that there is a significant relationship between the analytical learning style and the achievement of the competence read various types of texts in their mother tongue in high school students of the educational institution. For the study procedures, the field, cross-sectional and bivariate design was considered with the type of relational research, the population being 379 students and the sample 100. To collect information on the variables in the students, the survey was applied as a technique, a questionnaire and a written test as data collection instruments. In conclusion, there is a relationship between the analytical learning style and the achievement of competence, read various types of texts in their mother tongue because there are 6 (6.0%) with reading achievement at the beginning and with learning style inadequate analytical. In 40 (40.0%) with an achievement level in process, 2.0% (n=2) apply the appropriate analytical learning style and it is inadequate in 38.0% (n=38). In 45.0% (n=45) of the students with expected achievement, the analytical learning style is adequate in 14.0% (n=14) and inadequate in 31.0% (n=31). And in 9 (9.0%) with outstanding learning achievement in reading various types of texts, the analytical learning style is adequate in 7.0% (n=7) and inadequate in 2.0% (n=2).